(untitled) (Conferencea, 2022)
The article considers lexical competence as a part of linguistic competence. The composition of lexical competence includes the following components: motivational, cognitive, activity-practical and reflective. The level of formation of lexical competence is the ability of students to solve problems related to the assimilation of a foreign word in the practical use of it in speech on the basis of acquired knowledge and relevant skills.